Stigmatic Factors in Sexual Abuse and the Violence of Representation - Levett, Ann (PINS-Psychology in Society, 2026)
There are four points to the argument which follows about child sexual abuse, rape and sexual assault (all referred to here as "sexual abuse"). The most common and widespread consequence of this kind of abuse in westernized societies is stigma. Stigma is not a simple matter of labelling, or being labelled, although it includes these. It is a major factor in the process referred to as "psychological trauma·, a complex subjective experience with a set of potent social meanings, also self-imposed. The stigma of sexual abuse constitutes a false boundary or barrier of difference between women who are known to have been and those who are not known to have been - or do not know they have been - sexually abused; it has paradoxical consequences in everyday life. Although no purposeful conspiracy is involved, this false barrier serves to divide women and to protect male power. There is a relationship between stigmatic effects, the silence of those subjected to sexual abuse, and the social control of women by men. Finally, the very notion of psychological trauma (or damage) as the only, major and universal consequence of sexual abuse is a text of stigmatization which in itself constitutes a violence of representation.